Trypanocidal Activity and Increased Solubility of Benznidazole Incorporated in PEG 4000 and Its Derivatives - Sousa, Lucas Resende Dutra (2021)
Universidade Federal de Ouro Preto. Instituto de Ciências Exatas e Biológicas. Departamento de Química. Ouro Preto, MG, Brazil